tgx=ctgx
tgx=1/tgx
tg^2(x)=1 =>tgx=1=> x=arctg 1+Пn,n принадлежит => x= п/4+пn,n принадлежит Z
S={п/4+пn|n принадлежит Z}
3cos2x+sin^2(x)+5sinxcosx=0
3cos2x+sin^2(x)+5sinxcosx=0
3(2cos^2(x)-1)+sin^2(x)+5sinxcosx=0
6cos^2(x)-3sin^2(x)-3cos^2(x)+sin^2(x)+5sinxcosx=0|:cos^2(x) неравный 0
6-3tg^2(x)-3+tg^2(x)+5tgx=0
Пусть t=tgx,тогда
2t^2-5t-3=0
D=25-4*2*(-3)=25+24=49
t=(5-7)/4 t=-1/2 tgx=-1/2 x=-arctg1/2+Пn,n принадлежит Z
или или или или
t=(5+7)/4 t=3 tgx=3 x=arctg3+Пk,k принадлежит Z
Объяснение:
1) 1,5y=1,2-2,5=-1,3
y=2,6
5x+2,6=2
5x=-0,6
x=-6/50
2) 3+y=7
y=7-3=4